2017
DOI: 10.1089/mdr.2016.0205
|View full text |Cite
|
Sign up to set email alerts
|

Rectal Carriage of Extended-Spectrum Beta-Lactamase and Carbapenemase Producing Gram-Negative Bacilli in Intensive Care Units in Tunisia

Abstract: This study was conducted to evaluate the rate of fecal carriage of Gram-negative bacilli (GNB) resistant to third-generation cephalosporins (third GC) in patients hospitalized in the intensive care unit (ICU) of Charles Nicolle Hospital of Tunis and to identify the enzymatic mechanisms involved. From February to April 2014, rectal swabs were collected from all patients (n = 38) at admission and once weekly thereafter to identify acquisition. They were cultured on desoxycholate-lactose-agar plates supplemented … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

3
9
0

Year Published

2017
2017
2023
2023

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 23 publications
(12 citation statements)
references
References 49 publications
3
9
0
Order By: Relevance
“…The applied panel of multiplex PCRs identified carbapenemases in altogether 170/197 (86.3%) assessed Enterobacteriacae from the Military Hospital of Tunis. Similar to previous analyses [24, 25], the genes bla OXA-48 and bla NDM were most frequently detected with an overwhelming quantitative dominance of bla OXA-48 . In contrast, bla BIC and bla VIM were only sporadically observed, and the remaining 7 carbapenemase genes which were covered by the in-house PCR approaches were not detected at all.…”
Section: Discussionsupporting
confidence: 87%
See 1 more Smart Citation
“…The applied panel of multiplex PCRs identified carbapenemases in altogether 170/197 (86.3%) assessed Enterobacteriacae from the Military Hospital of Tunis. Similar to previous analyses [24, 25], the genes bla OXA-48 and bla NDM were most frequently detected with an overwhelming quantitative dominance of bla OXA-48 . In contrast, bla BIC and bla VIM were only sporadically observed, and the remaining 7 carbapenemase genes which were covered by the in-house PCR approaches were not detected at all.…”
Section: Discussionsupporting
confidence: 87%
“…During an assessment at a hospital in Tunis for about 3 months in 2014, 19 Gram-negative strains with resistance against 3rd generation cephalosporins were isolated from rectal swabs of 14 out of 31 patients (45.2%), one week after admission to hospital. Of note, rectal swabs of the same patients had been negative at the time of admission, indicating either nosocomial transmission as suggested by the authors of the study [25] or, alternatively, selection under the selective pressure of antibiotic treatment [26]. Identified ESBL genes comprised bla CTX-M-14 , bla CTX-M-15 , and bla GES-2 , while also carbapenemase genes, namely, bla GES-11 , bla NDM-1 , bla OXA-23 , and bla OXA-48 were identified [25].…”
Section: Introductionmentioning
confidence: 64%
“…In Tunisia, the dissemination of carbapenemases of Ambler class D in A. baumannii has been reported in a few studies (Mansour et al 2008;Hammami et al 2011Hammami et al , 2017Charfi-Kessis et al 2014;Chihi et al 2016). In 2013, Bonnin et al reported the finding of an A. baumannii isolate carrying the NDM-1 determinant isolated from a Tunisian patient hospitalized in France (Bonnin et al 2013).…”
Section: Introductionmentioning
confidence: 99%
“…The high proportion of these two species among ESBL-PE is the cause of treatment failure for the infections that they may cause. Most studies on ESBL-PE carriage have shown a predominance of E. coli which may carry genes located on plasmids encoding the production of ESBLs, that could facilitate transfer to other enterobacteria (4,15). The ESBL-PE showed resistance to meropenem of 47.4% and 22.4% respectively among hospitalized patients and healthy volunteers.…”
Section: Discussionmentioning
confidence: 99%